2009
DOI: 10.1086/648102
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Causation

Abstract: We have argued elsewhere that natural selection is not a cause of evolution, and that a resolution-of-forces (or vector addition) model does not provide us with a proper understanding of how natural selection combines with other evolutionary influences. These propositions have come in for criticism recently, and here we clarify and defend them. We do so within the broad framework of our own 'hierarchical realization model' of how evolutionary influences combine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Manipulating a man's marital status would certainly change whether he is a bachelor or not, but it is not because they are causally related, but rather logically the same. According to Matthen and Ariew (2009), the same applies to the interventions proposed by the causalists. Although manipulating, say, the fitness variance may affect evolutionary changes, it is just because they are the logically same thing -a variation in fitness is evolution.…”
Section: Fitness-evolution Relationship: Causal or Identical?mentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulating a man's marital status would certainly change whether he is a bachelor or not, but it is not because they are causally related, but rather logically the same. According to Matthen and Ariew (2009), the same applies to the interventions proposed by the causalists. Although manipulating, say, the fitness variance may affect evolutionary changes, it is just because they are the logically same thing -a variation in fitness is evolution.…”
Section: Fitness-evolution Relationship: Causal or Identical?mentioning
confidence: 99%
“…Although the charge made by Matthen and Ariew (2009) may be dismissed as ungrounded, it does not automatically vindicate the causalism. To prove some variables to be causes of evolution, it must be shown that an intervention on those variables is well defined and effectively affects the evolutionary response.…”
Section: Causes Of Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The idea is captured by an analogy offered by Matthen and Ariew (2009). Suppose two particles, p 1 and p 2 , in a container are moving away from one another at a constant velocity, such that their centre of mass, c, remains at a constant location with respect to the container.…”
Section: Natural Selection Is a Higher Order Effectmentioning
confidence: 99%
“…Unlike Grene, contemporary statisticalists also argue for Positive Claim #2-while MS-models do not identify the causes of population change, they are nevertheless genuinely explanatory (Matthen and Ariew 2002;Walsh, Lewens, and Ariew 2002). Statisticalists are thus committed to a class of statistical, non-causal explanations (Ariew et al 2014;Walsh 2013Walsh , 2015Matthen and Ariew 2009). 9 The plausibility of statisticalism rests on its ability to demonstrate that while change in trait distribution is caused by the capacities of individual organisms to survive and reproduce, it is nevertheless explained (and not caused) by the statistical properties (fitnesses) of abstract trait types.…”
mentioning
confidence: 99%